2015
DOI: 10.1007/s00221-015-4365-y
|View full text |Cite
|
Sign up to set email alerts
|

Interaction in planning movement direction for articulatory gestures and manual actions

Abstract: Some theories concerning speech mechanisms assume that overlapping representations are involved in programming certain articulatory gestures and hand actions. The present study investigated whether planning of movement direction for articulatory gestures and manual actions could interact. The participants were presented with written vowels (Experiment 1) or syllables (Experiment 2) that were associated with forward or backward movement of tongue (e.g., [i] vs. [ɑ] or [te] vs. [ke], respectively). They were req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 19 publications
6
29
1
Order By: Relevance
“…This is because [ae], which was how the participants mostly mispronounced [ɑ] as, is a front vowel, as is [i]. Indeed, we have recently shown a similar congruency effect between front-back hand movements and articulations [11]. The grip effect could actually be a manifestation of the same phenomenon.…”
Section: Discussionmentioning
confidence: 68%
“…This is because [ae], which was how the participants mostly mispronounced [ɑ] as, is a front vowel, as is [i]. Indeed, we have recently shown a similar congruency effect between front-back hand movements and articulations [11]. The grip effect could actually be a manifestation of the same phenomenon.…”
Section: Discussionmentioning
confidence: 68%
“…We have recently demonstrated that forward and backward hand movements can be influenced by pronouncing a speech unit during the hand movement (Vainio et al, 2015). In this forward/backward congruency effect, participants move their hand faster forward when pronouncing [i] rather than [α] or [o].…”
Section: Introductionmentioning
confidence: 99%
“…That is, the consonant [t] in which the air-flow is blocked with the tip of the tongue was linked to push movements whereas [k] in which air-flow is blocked with the body of the tongue was linked to pull movements. Consequently, the results suggested that the front-back position of the tongue was the critical factor for the effect to arise (Vainio et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations